Valida????o do teste de atividade de vida di??ria-Glittre para avaliar a capacidade funcional de indiv??duos com hemiparesia decorrente de acidente vascular encef??lico - Costa, Glaucio Carneiro (2016)
The Glittre AVD test (TGlittre) is a specific test to evaluate functional limitation in patients with chronic obstructive pulmonary disease, but it is not known whether it can be used to assess the capacity and performance of post-stroke patients. Objectives: To analyze the validation of TGlittre construct for hemiparetic patients due to stroke. METHODS: construct validity was analyzed using classical psychometry that established the use of well defined statistical methods, 30 hemiparetic adults after stroke and 20 healthy adults, matched in gender and age, according to eligibility criteria. The results were correlated to the 6-min walk test (TC6), time up and go (TUG) and functional independence measure scale (MIF) to analyze construct validity. The tests were randomized, performed on two consecutive days by the same evaluator. Data were submitted to the Shapiro Wilk normality test. The time of execution of the test between the groups was compared by the Mann-Whitney test. RESULTS: There was a strong and significant correlation between the AVD-Glittre versus the 6MT (r = -0.91, p <0.001), TUG (r = 0.82, p <0.001) 0.47, p <0.008). Conclusions: The AVD-Glittre was valid for evaluation of functional capacity and performance of hemiparetic patients after stroke. The Glittre AVD test is reliable when correlated with other tests already validated under different health conditions.